Existence of positive solutions for singular p-Laplacian Hadamard fractional differential equations with the derivative term contained in the nonlinear term - Guo, Limin; Liu, Haimei; Li, Cheng; Zhao, Jingbo; Xu, Jiafa (Nonlinear Analysis: Modelling and Control, 2023)
In this paper, based on the properties of Green function and the eigenvalue of a corresponding linear operator, the existence of positive solutions is investigated by spectral analysis for a infinite-points singular p-Laplacian Hadamard fractional differential equation boundary value problem, and an example is given to demonstrate the validity of our main results.